Gender characteristics of the reaction to the training load of athletes specializing in handto-hand combat with partial contact with the opponent - Stefyuk, I.; Kochyna, M.; Kochin, O. (Slobozhanskyi herald of science and sport, 2020)
Purpose: is to compare changes in the psychophysiological characteristics of male and female athletes with different levels of training under the influence of training load. Material and methods: the study involved 66 athletes, 42 of them were male and 24 were female, with different levels of training. We determined psychodynamic characteristics in athletes before and after training load with the help of standard methods. Results: we defined the dynamics of psychophysiological characteristics in athletes caused by training load. The trained athletes showed a state of mobilization evidenced by a significant decrease in strength and mobility of nervous processes.There were no reliable changes in male beginners engaged in hand-to-hand combat. The trained female athletes showed no significant differences in the indicators before and after training load, but the female beginners significantly decreased all psychodynamic characteristics. Conclusions: the obtained data showed some gender differences in the reaction to the training load in athletes specializing in hand-to-hand combat with a semi-contact. The training load led to the development of mobilization in trained athletes, while beginners of both sexes developed fatigue. There were no significant changes in the performance of the trained athletes.